⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ x + y + z x 2 + y 2 + z 2 x 3 + y 3 + z 3 x 5 + y 5 + z 5 = 1 = 2 = 3 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
From the given equations we get x y + y z + z x = − 2 1 , x y z = 6 1 . So x , y , z are the roots of the equation X 3 − X 2 − 2 1 X − 6 1 = 0 . Therefore x 4 + y 4 + z 4 = x 3 + y 3 + z 3 + 2 1 ( x 2 + y 2 + z 2 ) + 6 1 ( x + y + z ) = 3 + 1 + 6 1 = 6 2 5 and x 5 + y 5 + z 5 = x 4 + y 4 + z 4 + 2 1 ( x 3 + y 3 + z 3 ) + 6 1 ( x 2 + y 2 + z 2 ) = 6 2 5 + 2 3 + 6 2 = 6 2 5 + 9 + 2 = 6
Problem Loading...
Note Loading...
Set Loading...
Let P n = x n + y n + z n , where n is a positive integer, and S 1 = x + y + x = P 1 , S 2 = x y + y z + z x , and S 3 = x y z . By Newton's identities or Newton's sums , we have:
P 1 P 2 P 3 P 4 P 5 = S 1 = 1 = S 1 P 1 − 2 S 2 = 1 − 2 S 2 = 2 = S 1 P 2 − S 2 P 1 + 3 S 3 = 2 + 2 1 + 3 S 3 = 3 = S 1 P 3 − S 2 P 2 + S 3 P 1 = 3 + 1 + 6 1 = 6 2 5 = S 1 P 4 − S 2 P 3 + S 3 P 2 = 6 2 5 + 2 3 + 3 1 = 6 Given ⟹ S 2 = − 2 1 ⟹ S 3 = 6 1